1997
DOI: 10.1007/s000110050174
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of the novel COX-2 preferring NSAID, meloxicam in mono-arthritic rats: Central and peripheral components

Abstract: Systemic meloxicam produces analgesia largely via peripheral mechanisms. The rapidity of its actions indicates a direct effect on sensitised nociceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 21 publications
3
37
0
1
Order By: Relevance
“…Effects of pharmacological interventions on changes in the joint An important earlier paper by Laird et al [31] reported that in the same model as used in the present study daily administration of meloxicam i.p. reduced post-mortem analysis of ankle circumference and reduced the number of animals showing resistance to joint flexion and extension.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Effects of pharmacological interventions on changes in the joint An important earlier paper by Laird et al [31] reported that in the same model as used in the present study daily administration of meloxicam i.p. reduced post-mortem analysis of ankle circumference and reduced the number of animals showing resistance to joint flexion and extension.…”
Section: Discussionmentioning
confidence: 80%
“…Meloxicam is a potent antiinflammatory agent that is commonly prescribed to treat arthritic conditions [29,30]. Moreover, inhibition of COX-2 has beneficial effects on nociceptive scores in animal models of inflammatory joint disease [31][32][33]. However, most studies have examined only the effects of acute inhibition of COX-2 [32,33] and longer treatment regimens measured effects only during the early phase of model development and on a restricted number of functional readouts.…”
Section: Introductionmentioning
confidence: 99%
“…Meloxicam was also more potent in reducing edema of the inflamed rat paw than indomethacin, piroxicam, diclofenac, or naproxen (Engelhardt et al, 1995;Engelhardt, 1996) and produced analgesia in rat and dog models of inflammatory pain (Cross et al, 1997;Laird et al, 1997;Santos et al, 1998). At therapeutic doses of 7.5 or 15 mg, meloxicam did not reduce platelet aggregation or prolong bleeding time ex vivo (Stichtenoth et al, 1997;De Meijer et al, 1999;Panara et al, 1999;Tegeder et al, 1999), although thromboxane formation by platelets was inhibited by 35% after 15 mg of meloxicam.…”
Section: A Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…The selection of the meloxicam dose of 5 mg/kg b.w. was based on reports published by Laird et al (21), who used the compound in rats at doses of 0.1-4mg/kg b.w., every day for 5 days, and on the report published by Bourque et al (7), who administered MLX at the dose of 1-2 mg/kg b.w. every day for 3 days, subcutaneously.…”
Section: Discussionmentioning
confidence: 99%